ANALISIS PUTUSAN HAKIM TERHADAP PERKARA CERAI GUGAT DAN DAMPAK HUBUNGAN JARAK JAUH DALAM PERNIKAHAN - Fitri Ramadani; Nurul Fatiha Sadir (IAI DDI Mangkoso, 2024)
The purpose of this study is to analyze the judge's decision in divorce cases and the impact of long-distance relationships in marriage. The main focus of this study is to explore the factors that judges consider in deciding divorce cases and how long-distance relationships can affect marriages. The research method used is a qualitative method with a case study approach. Data was collected through interviews with informants. The results of the study show that in deciding a divorce lawsuit, the judge considers various factors such as the reason for filing for divorce, economic conditions, and the interests of the child. Regarding the impact of long-distance relationships, this study found that it can cause communication problems, lack of intimacy, and difficulties in resolving conflicts. However, some couples are able to adapt and maintain their marriage despite being in a long-distance relationship. This research provides important implications for the practice of family law and marriage counseling in handling issues related to divorce, lawsuits, and long-distance relationships.